2021
DOI: 10.1038/s41419-021-04437-6
|View full text |Cite
|
Sign up to set email alerts
|

LncTRPM2-AS inhibits TRIM21-mediated TRPM2 ubiquitination and prevents autophagy-induced apoptosis of macrophages in asthma

Abstract: Long non-coding RNAs (lncRNAs) play a crucial role in macrophage development but little is known about their role in asthma. Here, we investigated the role of lncRNA lncTRPM2-AS in asthma and found that lncTRPM2-AS participates in the promotion of macrophage inflammation. Downregulation of lncTRPM2-AS promoted apoptosis and inhibited proliferation and production of cytokines including IL-1β, IL-4, IL-6, IL-10, TNF-α, and TGF-β. RNA-immunoprecipitation and mass spectrometry indicated that the protein TRPM2 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Recently, more and more studies have also identified the ubiquitination as a central process in the pathogenesis and development of asthma [ 23 , 25 ]. Ubiquitination also indirectly participated in the pathogenesis of asthma through regulating functions of macrophage and dendritic cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have also identified the ubiquitination as a central process in the pathogenesis and development of asthma [ 23 , 25 ]. Ubiquitination also indirectly participated in the pathogenesis of asthma through regulating functions of macrophage and dendritic cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that autophagy also regulates macrophage apoptosis and further affects inflammation in asthma. A recent study has revealed that the lncRNA TRPM2-AS can inhibit autophagy-mediated apoptosis in macrophages by suppressing the TRIM21 (tripartite motif containing 21, an E3 ubiquitin ligase)-induced TRPM2 ubiquitination and further decreasing ROS levels, thus reducing the release of cytokines including IL-1 β , IL-4, IL-6, IL-10, TNF- α , and TGF- β in asthma [ 73 ]. These findings indicate that repression of macrophage autophagy promotes the inflammatory responses in asthma, which are associated with mitochondrial ROS accumulation.…”
Section: Effects Of Modulating Macrophage Autophagy On Asthmamentioning
confidence: 99%
“…[67] In intracellular immunity, TRIM21 was strongly reported to modulate the stability and activity of IRFs positively or negatively via ubiquitination, reportedly including IRF3, IRF5, IRF7, and IRF8 (Figure 3). Thereby, TRIM21 indirectly influence the level of cytokines in IRFs driven way, contributing to regulation of genes such as type I IFN (IFN-𝛼, IFN-𝛽), type II IFN (IFN-𝛾), IL-6, IL12, IL-12p40, and then differentiation of immune cell, mostly containing lymphocytes, [47,[68][69][70] macrophage, [61,66,71,72] mononuclear cells, [60,73] and so on. As the historical marker of autoimmune diseases, recent studies suggested TRIM21 was overexpressed in patient with SLE and induced ubiquitination of IRF3, IRF5, and IRF7, therefore enhancing the synthesis of type I IFN.…”
Section: Irfsmentioning
confidence: 99%